2023
DOI: 10.1186/s13098-023-01132-8
|View full text |Cite|
|
Sign up to set email alerts
|

Syndecan-4 as a genetic determinant of the metabolic syndrome

Abstract: Background Syndecan-4 (SDC4) is a member of the heparan sulfate proteoglycan family of cell-surface receptors. We and others previously reported that variation in the SDC4 gene was associated with several components of the metabolic syndrome, including intra-abdominal fat, fasting glucose and triglyceride levels, and hypertension, in human cohorts. Additionally, we demonstrated that high fat diet (HFD)-induced obese female mice with a Sdc4 genetic deletion had higher visceral adiposity and a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Recent evidence strongly suggests that SCD4 plays a pivotal role in the control of body composition by regulating processes related to fat storage, muscle development, and bone fracture repair [ 11 15 ]. For instance, genetic studies in mice harboring a Sdc4 global knockout allele demonstrated that SDC4 deficiency promotes diet and sex-specific changes in percentage of body fat and lean mass and metabolic outcomes [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence strongly suggests that SCD4 plays a pivotal role in the control of body composition by regulating processes related to fat storage, muscle development, and bone fracture repair [ 11 15 ]. For instance, genetic studies in mice harboring a Sdc4 global knockout allele demonstrated that SDC4 deficiency promotes diet and sex-specific changes in percentage of body fat and lean mass and metabolic outcomes [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%